2013
DOI: 10.1681/asn.2012070700
|View full text |Cite
|
Sign up to set email alerts
|

Vps34 Deficiency Reveals the Importance of Endocytosis for Podocyte Homeostasis

Abstract: The molecular mechanisms that maintain podocytes and consequently, the integrity of the glomerular filtration barrier are incompletely understood. Here, we show that the class III phosphoinositide 3-kinase vacuolar protein sorting 34 (Vps34) plays a central role in modulating endocytic pathways, maintaining podocyte homeostasis. In mice, podocyte-specific conditional knockout of Vps34 led to early proteinuria, glomerular scarring, and death within 3-9 weeks of age. Vps34-deficient podocytes exhibited substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
111
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 62 publications
13
111
1
1
Order By: Relevance
“…PI3P was reported to affect receptor sorting, through its interaction with the ESCRT-0 Hrs protein, but not bulk transport (Petiot et al, 2003). However, in podocytes from the phosphatidylinositol 3-kinase Vps34-invalidated mice, both receptor-mediated endocytosis and fluidphase uptake are compromised at the level of Rab5 and EEA1-positive early endosomes (Bechtel et al, 2013). It is interesting to note that, in our model, contrary to a loss of PI3P, a strong increase in PI5P leads to the blockade.…”
Section: Discussionmentioning
confidence: 99%
“…PI3P was reported to affect receptor sorting, through its interaction with the ESCRT-0 Hrs protein, but not bulk transport (Petiot et al, 2003). However, in podocytes from the phosphatidylinositol 3-kinase Vps34-invalidated mice, both receptor-mediated endocytosis and fluidphase uptake are compromised at the level of Rab5 and EEA1-positive early endosomes (Bechtel et al, 2013). It is interesting to note that, in our model, contrary to a loss of PI3P, a strong increase in PI5P leads to the blockade.…”
Section: Discussionmentioning
confidence: 99%
“…167,168 However, studies from several Pik3c3 knockout animal models suggest that PtdIns3P generation and autophagic function rely predominantly on PIK3C3 activity. 111,169,170 The question of whether class III PtdIns3K is the exclusive kinase responsible for PtdIns3P generation during autophagy remained unsolved until a recent study by Devereaux et al revealed an alternative source of PtdIns3P in Pik3c3 knockout MEFs. 171 In Pik3c3 KO MEFs, it is surprising that PtdIns3P is still detectable using a higher affinity PtdIns3P probe and the PtdIns3P-binding protein WIPI1, and autophagosomes are still observed under starvation conditions; class II PI3K was confirmed as another contributor to the PtdIns3P pool during autophagy, and depletion of class II PI3K further decreases autophagic flux, which is inhibited by Pik3c3 deletion.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%
“…17,18 In addition, recent studies have reported that podocytes exert a higher level of autophagy under basal conditions and that autophagy significantly contributes to maintaining the functional integrity of podocytes. [19][20][21][22][23][24] Considering the importance of CD in neuronal autophagy and the resemblance between neurons and podocytes, we hypothesized that it is of particular importance to elucidate the role of CD in podocytes. In this study, we investigated the effects of CD deficiency on podocyte structure and function using podocytespecific, CD-deficient mice.…”
mentioning
confidence: 99%